Genetic mapping and candidate gene analysis for melon resistance to Phytophthora capsici - Pingyong Wang (Nature Portfolio, 2020)
Abstract Phytophthora blight is one of the most serious diseases affecting melon (Cucumis melo) production. Due to the lack of highly resistant germplasms, the progress on disease-resistant research is slow. To understand the genetics of melon resistance to Phytophthora capsici, an F2 population containing 498 individuals was developed by crossing susceptible line E31 to highly resistant line ZQK9. Genetic analysis indicated that the resistance in ZQK9 was controlled by a dominant gene, tentatively named MePhyto. Through bulked-segregant analysis (BSA-Seq) and chromosome walking techniques, the MePhyto gene was mapped to a 52.44 kb interval on chromosome 12. In this region, there were eight genes and their expression patterns were validated by qRT-PCR. Among them, one wall-associated receptor kinase (WAK) gene MELO3C002430 was significantly induced in ZQK9 after P. capsici inoculation, but not in E31. Based on the non-synonymous mutation site in MELO3C002430, a cleaved amplified polymorphic sequence (CAPS) marker, CAPS2430, was developed and this maker was co-segregated with MePhyto in both F2 population and a collection of 36 melon accessions. Thus MELO3C002430 was considered as the candidate gene and CAPS2430 was a promising marker for marker-assisted selection (MAS) in breeding. These results lay a foundation for revealing the resistance mechanism of melon to P. capsici.